Microstructure evolution and mechanical properties of Ti2AlNb/TiAl brazed joint using newly-developed Ti–Ni–Nb–Zr filler alloy - Xinyu Ren (Progress in Natural Science: Materials International, 2020)
Joining of Ti2AlNb alloy to TiAl intermetallics was conducted by the newly-developed Ti–Ni–Nb–Zr brazing filler alloy. The microstructure evolution of the joints was investigated by scanning electron microscope (SEM), energy dispersive spectrometer (EDS) and electron backscatter diffraction (EBSD). The macro-micro mechanical properties were studied by shear test and nano-indentation test. Typical interfacial microstructures across the brazing seam were Ti2AlNb substrate, α2-Ti3Al+β-Ti, γ-TiAl+Ti2Ni+TiNi+α2-Ti3Al, α2-Ti3Al+β-Ti, TiAl substrate. The Ti2Ni phase were firstly dissolved in the joints brazed at 1000 °C for 10 min and then precipitated after a prolonged holding time of 15 min. The nano-indentation test revealed that Ti2Ni phase exhibited the highest hardness of 12.60 GPa. The joints brazed at 1000 °C/15 min presented the maximum shear strength of 271 MPa. The dissolution and precipitation behavior of Ti2Ni phase was also discussed.